Atypical small acinar proliferation and its significance in pathological reports in modern urological times - Georgios Tsampoukas; Victor Manolas; Dominic Brown; Athanasios Dellis; Konstantinos Deliveliotis; Mohamad Moussa; Athanasios Papatsoris (Asian Journal of Urology)
Atypical small acinar proliferation is a histopathological diagnosis of unspecified importance in prostate needle-biopsy reports, suggestive but not definitive for cancer. The terminology corresponds to some uncertainty in the biopsy report, as the finding might represent an underlying non-cancerous pathology mimicking cancer or an under-sampled prostate cancer site. Therefore, traditional practice favors an immediate repeat biopsy. However, in modern urological times, the need of urgent repeat biopsy is being challenged by some authors as in the majority of cases, the grade of cancer found in subsequent biopsy is reported to be low or the disease to be non-significant. On the other hand, high risk disease cannot be excluded, whereas no clinical or pathological factors can predict the final outcome. In this review, we discuss the significance of the diagnosis of atypical small acinar proliferation in the biopsy report, commenting on its importance in modern urological practice.